Unexpected coseismic surface uplift at Tirúa-Mocha Island area of south Chile before and during the Mw 8.8 Maule 2010 earthquake: a possible upper plate splay fault - Quezada, Jorge (2020)
The Tirúa-Mocha Island area (38.2°-38.4° S) in southern Chile has been affected by two megaearthquakes in only 50 years: the 1960 Mw=9.5 Valdivia earthquake and 2010 Mw=8.8 Maule earthquake. We studied in the field the vertical ground movements occurred during the interseismic period between both earthquakes and the coseismic period of 2010 Maule earthquake and 2011 Mw=7.1 Araucanía earthquake. During the 1960 earthquake, vertical coseismic ground movements are typical of subduction related earthquakes with Mocha Island, located close to the trench, experienced bigger ground uplift (150 cm) than that occurred in Tirúa (-20 cm), place located in the continental margin at the latitude of Mocha Island. Then during the 1960-2010 interseismic period, the 1960 coseismic uplift remained at Mocha Island unlike the normal interseismic subsidence that occurred northward at Arauco Peninsula and Santa María Island. Also Tirúa experienced the biggest interseismic uplift (180 cm) in all the area affected later by 2010 Maule earthquake. Then during the 2010 Mw=8.8 Maule earthquake an anomalous vertical coseismic ground uplift occurred in the study area, opposite to that of 1960 since Mocha Island experienced lower (25 cm) ground uplift than Tirúa (90 cm). Subsequently, during the Araucanía 2011 earthquake a ground uplift in Mocha Island (50 cm) and subsidence at Tirúa (20 cm) occurred. These unexpected vertical ground movements can be explained by the existence of an upper plate splay fault located below the sea bottom between Tirúa and Mocha Island: the Tirúa-Mocha splay fault. Considering the last seismic cycle, the activity of this fault would have started after the 1960 Valdivia earthquake. During 2010 Maule earthquake, the main slip occurred at Tirúa Mocha splay fault. Finally during 2011 Araucanía earthquake, the slip occurred mainly at the updip of Wadati-Benioff plane with probable normal activity of Tirúa-Mocha splay fault. Simple elastic dislocation models considering the Wadati-Benioff plane and the Tirúa-Mocha splay fault activity, can account for all the vertical ground movements observed during 1960 earthquake, the 1960-2010 interseismic period, the 2010 Maule earthquake and the 2011 Araucanía earthquake.